Catalyst design criteria and fundamental limitations in the electrochemical synthesis of dimethyl carbonate. Issue 22 (30th October 2019) - Šarić, Manuel; Davies, Bethan Jane Venceslau; Schjødt, Niels Christian; Dahl, Søren; Moses, Poul Georg; Escudero-Escribano, María; Arenz, Matthias; Rossmeisl, Jan
Abstract : Electrocatalytic formation of DMC and DMO via different surface bound intermediates. Abstract : Dimethyl carbonate is an environmentally friendly precursor in various chemical reactions and is currently synthesized by hazardous processes. An electrocatalytic approach could result in a process abiding to the principles of Green Chemistry. Herein we demonstrate how density functional theory (DFT) calculations and experiment advance our understanding of electrocatalytic production of chemicals. Using density functional theory, we form design criteria for dimethyl carbonate electrosynthesis on metallic surfaces. The criteria are based on adsorption free energies of reactants and reaction energies of possible products. The design criteria allow us to identify copper as an interesting candidate for the electrode material as it is classified as being selective to dimethyl carbonate and requires ≈1 V lower potential than a gold electrode. By further addressing electrode stability copper was found to dissolve and produce copper-carbonyl species which lead to dimethyl carbonate as a consequence of a reaction in the solution, therefore not occurring by surface electrocatalysis. This shows that the design criteria presented herein are necessary but not sufficient requirements that the ideal electrode should satisfy.